Antibacterial power Village Fowl Egg Albumen (Gallus domesticus) and Kate chicken (Gallus Bantam) against fecal Coliform Bacteria Species at Eggshell Egg - Vera Pramesti Wijaya (Jurnal Pendidikan Sains, 2013)
Daya Antibakteri Albumen Telur Ayam Kampung (Gallus Domesticus) dan Ayam Kate (Gallus Bantam) terhadap Spesies Bakteri Coliform Fekal pada Cangkang Telur Abstract: This study aims to identify the species of fecal coliform bacteria found in chicken egg shells and Bantam and analyze the influence of chicken egg albumen and egg Bantam on the inhibition of the growth of species of fecal coliform bacteria found in chicken egg shells. This study is experimental with the independent variable in the form of chicken egg albumen and kate. The dependent variable in the form of growth inhibition zone fecal coliform bacteria. Tests performed by the agar diffusion method. Testing the antibacterial activity of chicken egg albumen and Bantam done by measuring the diameter of growth inhibition zone of each species colonies of fecal coliform bacteria in the medium Nutrient Agar. The research data is the measurement data growth inhibition zone diameter species of fecal coliform bacteria. Results were analyzed using analysis of variance single, and continued with LSD 1%. Results of the study are: (1) species fecal coliform bacteria found in chicken egg shells and chicken egg is Actinobacillus sp., Serratia liquefaciens, ozaenae Klebsiella, and Escherichia vulneris; and (2) there is the effect of different chicken egg albumen and egg Bantam towards the inhibition of the growth of species of fecal coliform bacteria found in chicken egg shells. Key Words: albumen of eggs, chicken, Bantam, antibacterial, fecal coliform bacteriaAbstrak: Penelitian ini bertujuan mengidentifikasi spesies-spesies bakteri koliform fekal yang terdapat pada cangkang telur ayam kampung dan ayam kate dan menganalisis pengaruh albumen telur ayam kampung dan telur ayam kate terhadap penghambatan pertumbuhan spesies-spesies bakteri koliform fekal yang terdapat pada cangkang telur ayam. Penelitian ini merupakan penelitian ekperimen dengan variabel bebas berupa albumen telur ayam kampung dan kate. Variabel terikat berupa zona hambat pertumbuhan bakteri koliform fekal. Pengujian dilakukan dengan metode difusi agar. Pengujian daya antibakteri albumen telur ayam kampung dan ayam kate dilakukan dengan mengukur diameter zona hambat pertumbuhan koloni tiap spesies bakteri koliform fekal pada medium Nutrien Agar. Data penelitian adalah data hasil pengukuran diameter zona hambat pertumbuhan spesies-spesies bakteri koliform fekal. Hasil penelitian dianalisis menggunakan analisis varian tunggal, dan dilanjutkan dengan uji BNT 1%. Hasil dari penelitian adalah: (1) spesies-spesies bakteri koliform fekal yang terdapat pada cangkang telur ayam kampung dan telur ayam yaitu Actinobacillus sp., Serratia liquefaciens, Klebsiella ozaenae, dan Escherichia vulneris; dan (2) ada pengaruh perbedaan albumen telur ayam kampung dan telur ayam kate terhadap daya hambat pertumbuhan spesies-spesies bakteri koliform fekal yang terdapat pada cangkang telur ayam.Kata kunci: albumen telur, ayam kampung, ayam kate, daya antibakteri, bakteri koliform fekal